2020
DOI: 10.1093/ofid/ofaa563
|View full text |Cite
|
Sign up to set email alerts
|

Role of Low-Molecular-Weight Heparin in Hospitalized Patients With Severe Acute Respiratory Syndrome Coronavirus 2 Pneumonia: A Prospective Observational Study

Abstract: Objectives To evaluate the impact of low molecular weight heparin (LMWH) on the outcome of patients with SARS-CoV-2 pneumonia. Methods Prospective observational study including consecutive patients with laboratory confirmed SARS-CoV-2 pneumonia admitted to the University Hospital of Pisa (4th March-30th April 2020). Demographic, clinical, and outcome data were collected. The primary endpoint was 30-day mortality. The secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 25 publications
0
73
0
Order By: Relevance
“…The role of heparins in the prevention and treatment of thromboembolic complications of COVID-19 has been widely established [ 11 , 12 ]. In a prospective, observational study involving 315 patients with laboratory-confirmed SARS-CoV-2 pneumonia, Falcone et al have shown that low-molecular-weight heparins (LMWHs) significantly reduced the risk of in-hospital mortality and severe acute respiratory distress syndrome [ 13 ]. Similarly, a nationwide cohort study of 4297 hospitalized patients in the US provided evidence that early initiation of prophylactic anticoagulation among patients hospitalized with COVID-19 was associated with a decreased risk of mortality [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of heparins in the prevention and treatment of thromboembolic complications of COVID-19 has been widely established [ 11 , 12 ]. In a prospective, observational study involving 315 patients with laboratory-confirmed SARS-CoV-2 pneumonia, Falcone et al have shown that low-molecular-weight heparins (LMWHs) significantly reduced the risk of in-hospital mortality and severe acute respiratory distress syndrome [ 13 ]. Similarly, a nationwide cohort study of 4297 hospitalized patients in the US provided evidence that early initiation of prophylactic anticoagulation among patients hospitalized with COVID-19 was associated with a decreased risk of mortality [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was regularly updated according to any new release from the scientific literature (Table S1 , available as Supplementary data at JAC Online). 5 Immunomodulant agents used in our hospital were tocilizumab and baricitinib. The decision to prescribe one of the two immunosuppressants was made by the attending physician.…”
Section: Methodsmentioning
confidence: 99%
“…An observational study including 2,773 patients hospitalized with laboratory-confirmed COVID-19 within the Mount Sinai Health System in New York City showed that systemic anticoagulation was associated with improved outcomes 6 . We recently found that low molecular weight heparin was the only therapeutic factor independently associated with survival in a propensity-score adjusted analysis on 315 patients with COVID-19 10 . As for other systemic diseases with high prevalence in older population, the prescription of an anticoagulation treatment should be weighed against the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Such anatomical alterations can contribute to the elevation of hsTnT independently from the severity of the inflammatory response, as they can further aggravate the delivery of an adequate oxygen supply to the myocardium. The importance of control the coagulatory homeostasis in COVID-19 is recently under attention as some studies have reported a beneficial effect of anticoagulation therapies in these patients 7 , 9 , 10 . However, beyond the large number of reports describing associations between hsTnT with mortality in COVID-19, no studies have comprehensively explored the relative contribution of coagulopathy, hypoxia and inflammation to the increase in hsTnT during SARS-CoV2 pneumonia, nor the importance of these pathways in defining the risk of mortality in COVID-19.…”
Section: Introductionmentioning
confidence: 99%